Presentism, truthmaking and necessary connections - Tallant, Jonathan (Wiley, 2015)
Ross Cameron puts forward a novel solution to the truthmaker problem facing presentism. I claim that, by Cameron's own lights, the view is not in fact a presentist view at all, but rather requires us to endorse a form of Priority Presentism, whereby past objects are derivative and depend for their existence upon present objects. I argue that this view should be rejected.